AN INVESTIGATION OF STYLISTIC DEVICES IN “THE GREAT GATSBY” OF FRANCIS SCOTT KEY FITZGERALD AND ITS VIETNAMESE TRANSLATION - Lê Thị Thúy Kiều (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2024)
Stylistic devices are one of popular tools in literature works. English literature, a useful source for English learners not only helps learners to understand the beauty of English language and stylistic devices but also improves their written language with regard to stylistic features. The thesis aims to make an objective analysis of stylistic devices in the famous novel – The Great Gatsby by Francis Scott Key Fitzgerald. The study results show not only the use of stylistic devices in 200 samples but also similarities and differences in the original and translational versions of The Great Gatsby. In terms of the plot of the novel, the translator conveyed the plot to the reader despite language barrier, cultural differences and writing styles. Moreover, the study provides implications regarding teaching and learning strategies involving stylistic devices.